2023
DOI: 10.3390/healthcare11091242
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Lasting Effects of Slow-Paced Breathing on Handball Team Coach’s Match Stress

Abstract: Stress was previously defined as a response to any demand for change. These demands are noticeable during sport events, not only in athletes but also in coaches. Therefore, this study aimed to determine the influence of slow-paced breathing (SPB) on acute stress to handball coaches during official matches. One professional handball coach, aged 37 (height, 180 cm; weight, 80 kg), took part in the study. His salivary cortisol (C) concentration and alpha-amylase (AA) activity were measured, and his heart rate (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…We begin with stress assessment, where the influence of slow breathing on acute stress among handball coaches was evaluated. It was indicated that implementing respiratory control could improve stress conditions during official games, with potential impacts on health [14].…”
mentioning
confidence: 99%
“…We begin with stress assessment, where the influence of slow breathing on acute stress among handball coaches was evaluated. It was indicated that implementing respiratory control could improve stress conditions during official games, with potential impacts on health [14].…”
mentioning
confidence: 99%